Rekonstruksi Kurikulum Pendidikan Agama Islam Berbasis Multikultural Dalam Penguatan Sikap Toleransi Siswa - Sri Wahyuni; Alzahra Fita Salsabella; Arrum Husaini Safitri; Dinda Auliya Safitri; Mursyidatul Hilmah; Niesa Amalia (Kariman: Jurnal Pendidikan Keislaman, 2026)
This study aims to analyze the reconstruction of a multicultural-based Islamic Religious Education (PAI) curriculum in strengthening students’ tolerance attitudes. The background of this study is based on the dominance of cognitive and normative approaches in PAI learning, which have not fully responded to the realities of Indonesia’s plural society. This condition creates a gap between the ideal goals of religious education and its practical implementation, thus requiring a more contextual and inclusive curriculum development. This research employs a qualitative approach using a literature review method by analyzing various sources related to Islamic and multicultural education, including recent academic journals, books, and relevant policy documents. The findings reveal that the multicultural-based PAI curriculum is grounded in humanism and progressivism, as well as theological foundations derived from the Qur’an and Sunnah. The curriculum design integrates values such as tolerance, justice, and respect for diversity into learning objectives, materials, methods, and evaluation. Its implementation applies dialogical, collaborative, and contextual approaches supported by active learning strategies. As a result, students demonstrate more inclusive, tolerant, and moderate attitudes. Therefore, reconstructing a multicultural-based PAI curriculum is a strategic effort to develop religious individuals who can live harmoniously in a diverse society and contribute positively to social cohesion.